Get your word across - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Selective Guide to Scientific Journals in the Field of Agriculture and Rural Development. Prepared by CIRAD, France and CABI, UK, for CTA. 1999. 203 pp. CTA number 8001. 0 credit point.